The δ18O and δD isoscapes of recent groundwater in Poland - Leśniak, Paweł M.; Wilamowski, Andrzej (Geologos, 2019)
Considering the country’s development and quality of life, recognition of the water cycle mechanism is of great importance. A significant contribution to this comes from the isotopic composition of particular elements of the water cycle. However, a weak point is that in Poland only one element of the water cycle, precipitation, is sampled and measured over more than 312 thousands km2 at a single station. It is therefore necessary to seek extension of or alternatives for these rare data. Such an alternative is the sampling of groundwater containing tritium in the national monitoring network of groundwater bodies that is maintained by the Polish Geological Institute. Based on such data we have constructed δ18O and δD isoscapes (i.e., maps of δ18O and δD values) of recent groundwater. These data provide spatial distribution of δ18O and δD values which can be used as input to hydrogeological models.